2020
DOI: 10.3390/jcm9113608
|View full text |Cite
|
Sign up to set email alerts
|

Balloon Pulmonary Angioplasty in Patients with Chronic Thromboembolic Pulmonary Hypertension: Impact on Clinical and Hemodynamic Parameters, Quality of Life and Risk Profile

Abstract: Balloon pulmonary angioplasty (BPA) is a novel treatment option for patients with chronic thromboembolic pulmonary hypertension (CTEPH) who are not eligible for pulmonary endarterectomy (PEA) or suffer from persistent pulmonary hypertension after PEA. The aim of this study was to evaluate the real-life efficacy and safety of BPA in a consecutive group of patients who were diagnosed and treated in the national referral center for CTEPH in the Czech Republic. Here we report data from 160 BPA procedures performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…5,8,10,16,33,49 BPA has been performed routinely in the Czech Republic since 2017 and a recent study that included 25 patients with CTEPH who completed their series of BPA procedures between 2013 and 2019 reported significant improvements in their NYHA FC, 6MWD, PVR and quality of life following the procedure (median of 4 months [95% CI: 2.0; 14.0] after the last BPA). 25 The strengths of this study are the national coverage afforded by the single national expert center, the use of comprehensive data from the national databases (IHIS CR), and the ability of the study to provide a basis for future studies by virtue of being conducted when PEA was the only treatment option. In this study, survival was estimated since diagnosis for all groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,8,10,16,33,49 BPA has been performed routinely in the Czech Republic since 2017 and a recent study that included 25 patients with CTEPH who completed their series of BPA procedures between 2013 and 2019 reported significant improvements in their NYHA FC, 6MWD, PVR and quality of life following the procedure (median of 4 months [95% CI: 2.0; 14.0] after the last BPA). 25 The strengths of this study are the national coverage afforded by the single national expert center, the use of comprehensive data from the national databases (IHIS CR), and the ability of the study to provide a basis for future studies by virtue of being conducted when PEA was the only treatment option. In this study, survival was estimated since diagnosis for all groups.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 8 , 10 , 16 , 33 , 49 BPA has been performed routinely in the Czech Republic since 2017 and a recent study that included 25 patients with CTEPH who completed their series of BPA procedures between 2013 and 2019 reported significant improvements in their NYHA FC, 6MWD, PVR and quality of life following the procedure (median of 4 months [95% CI: 2.0; 14.0] after the last BPA). 25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 The use of BPA in Europe is increasing but is being reported primarily in retrospective studies with few entries identified in the clinical trial databases. [19][20][21] (Table 1). In addition to BPA, our search identified pulmonary artery denervation as the subject of two clinical trials based in Russia and China, with results having been recently published by Romanov et al 22 Around one in four patients will have residual pulmonary hypertension after PEA and it remains unclear how best to integrate medical therapy or BPA.…”
Section: Discussionmentioning
confidence: 99%
“…A pulmonary endarterectomy (PEA) is the treatment of choice for operable patients. However, some patients are ineligible for surgery due to distal localization of thromboembolic lesions, comorbidities, or functional status [ 4 , 5 ]. Available treatment options for these CTEPH patients include targeted medical therapy and interventional technique—percutaneous balloon pulmonary angioplasty (BPA), which has become a promising treatment modality [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%